Antibacterial Activity of Compound TL-4 IFATL-05 Isolate Endophytic Fungi from Tunjuk Langit Root (Helminthostachys zeylanica (L.) Hook) Against Bacterial Gastrointestinal Tract Infection - Yuridu, Fatur Rahmansyah; Herwin, Herwin; Fitriana, Fitriana (Fakultas Farmasi, Universitas Muslim Indonesia, 2023)
Tunjuk Langit Plant (Helminthostachys zeylanica (L.) Hook) contains a lot of secondary metabolite compounds, one of which is found in the root which contain the flavonoids ugonin and quercetin. The purpose of this study was to determine the antibacterial activity of compound 4 isolates IFATL-05 endophytic fungi from Tunjuk Langit (Helminthostachys zeylanica (L.) Hook) root against bacterial gastrointestinal tract infection. The results of purification of endophytic fungi with IFATL-05 code on macroscopic examination showed blackish-white fungus color, round with scalloped colony shapes, wavy edges and drop-like elevation angles. The process of separating the compounds using KLTP with n-hexane:ethyl acetate (1:1) as an eluent resulted in four bands of active compounds in UV lamps of 254 and 366 nm (TL-1, TL-2, TL-3 and TL-4). Test results for compound 4 isolates of IFATL05 endophytic fungi from Tunjuk Langit root (Helminthostachys zeylanica (L.) Hook) using the Bioautographic TLC method using n-hexane:ethyl acetate (6:1) as eluent on Escherichia coli, Salmonella thypi, Shigella dysenteriae and Vibrio cholerae with Rf value = 0.90